Ảnh hưởng của các đặc tính phát trực tiếp (Livestream) tới hành vi mua hàng ngẫu hứng: Vai trò trung gian của niềm tin và trải nghiệm dòng chảy - Hoàng Văn, Tình; Đoàn Thanh, Hải (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2024)
This research aims to examine the effect of live-streaming characteristics on consumers’ impulsive buying behavior. The study adopts the stimulus–organism–response theory (S-O-R) as a theoretical framework and uses a self-administered questionnaire for data collection from 291 viewers experienced in watching live streaming. The data were analyzed using SmartPLS 3.0 software. The results indicate that personalization and entertainment positively influence consumers’ flow experience and trust; both flow experience and trust have positive impacts on impulsive purchases and mediate the relationships between personalization, entertainment, and impulsive buying behavior. These findings contribute to existing theoretical research on live-streaming commerce and offer practical implications for streamers and e-retailers.